The Electric Telegraph, News Coverage and Political Participation - Tianyi Wang (Institute of Labor Economics (IZA), 2023)
Using newly digitized data on the growth of the telegraph network in America during 1840-1852, the paper studies the impacts of the electric telegraph on national elections. I use proximity to daily newspapers with telegraphic connections to Washington to generate plausibly exogenous variation in access to telegraphed news from Washington. I find that access to Washington news with less delay significantly increased voter turnout in national elections. For mechanisms, I provide evidence that newspapers facilitated the dissemination of national news to local areas. In addition, text analysis on more than a hundred small-town weekly newspapers from the 1840s shows that the improved access to news from Washington led newspapers to cover more national political news, including coverage of Congress, the presidency, and sectional divisions involving slavery. The results suggest that the telegraph made newspapers less parochial, facilitated a national conversation and increased political participation. I find little evidence that access to telegraphed news from Washington affected party vote shares or Congressmen's roll call votes.
Keywords: O3; L96; L82; D72; N71; 330; information technology; newspaper; election; economic history